Diameter, strength and resistance tuning of double-walled carbon nanotubes in a transmission electron microscope. (30th April 2020) - Cheng, Yong; Li, Xin; Gao, Haowen; Wang, Jinming; Luo, Guangfu; Golberg, Dmitri; Wang, Ming-Sheng
Abstract: We report an atomic structure and property tailoring method that enables precise control of the diameter of individual double-walled carbon nanotubes (DWNTs), as well as the corresponding tuning of their tensile strength and electrical resistance. As demonstrated in a transmission electron microscope (TEM), this facile method involves the electron irradiation of DWNTs, followed by a thermal annealing process. The former process is responsible for the random atom loss and tube size reduction, whereas the latter allows for a complete structural recovery of defective nanotubes. The regarded DWNTs thus experience repeated disorder-order structural transitions, leading to the stepwise shrinkage in tube size, until the desired diameter is reached. Accordingly, these disorder-order transitions allow individual DWNTs to be controllably weakened and then strengthened, accompanied with the reversible changes in their breaking modes, as revealed by direct in-situ tensile tests. Differently, the resistance tuning of DWNTs upon irradiation/annealing does not follow the same trend, but depends significantly on the initial tube electrical characteristics and subsequent chirality transitions. These experimental results, combined with first-principles calculations, suggest that the change of tube chirality involved in the disorder-order transitions profoundly influences DWNT transport properties, but has a little impact on their mechanical strength. Graphical abstract: Image 1